Design of collectors in centrifugal spinning: Effect on the fiber yield and morphology - Naseri Joda, Nasrollah; Ince, Ahmet Erdem; Říhová, Martina; Pavliňák, David; Macák, Jan (SAGE PUBLICATIONS INC, 2024)
Centrifugal spinning is an increasingly popular and viable method to produce fibers of different compositions. However, there are still aspects to investigate and improve in the centrifugal spinning process, such as optimizing the fiber yield and obtaining defect-free fiber morphology. To address this gap, the effects of the collectors on the fiber yield and their morphology were investigated in this work. An aqueous solution with 18 wt% of PVP and two needles (18G and 21G) with different diameters and three different spinning speeds (5000, 7000, and 9000 RPM) were used to explore a set of fiber collectors with various collector spacing (1, 3, 6, 12, and 18 cm distance between the collectors' bars). The results of the experiments showed that fiber collectors affect the yield of the process and the fiber morphology to some (non-negligible) extent. Denser collectors enabled higher yield, thus reducing the waste, and positively affecting the beading of fibers. The knowledge obtained in this work about the influence of collectors on the centrifugal processing of basic polymers can be with an advantage applied to the processing of different polymers and needles used within the centrifugal spinning process.

Centrifugal spinning is an increasingly popular and viable method to produce fibers of different compositions. However, there are still aspects to investigate and improve in the centrifugal spinning process, such as optimizing the fiber yield and obtaining defect-free fiber morphology. To address this gap, the effects of the collectors on the fiber yield and their morphology were investigated in this work. An aqueous solution with 18 wt% of PVP and two needles (18G and 21G) with different diameters and three different spinning speeds (5000, 7000, and 9000 RPM) were used to explore a set of fiber collectors with various collector spacing (1, 3, 6, 12, and 18 cm distance between the collectors' bars). The results of the experiments showed that fiber collectors affect the yield of the process and the fiber morphology to some (non-negligible) extent. Denser collectors enabled higher yield, thus reducing the waste, and positively affecting the beading of fibers. The knowledge obtained in this work about the influence of collectors on the centrifugal processing of basic polymers can be with an advantage applied to the processing of different polymers and needles used within the centrifugal spinning process.
Design of collectors in centrifugal spinning: Effect on the fiber yield and morphology
Keywords: Centrifugal spinning; fibers yield; collector; needle; airflow; Centrifugal spinning; fibers yield; collector; needle; airflow